Biocompatible Chemistries for the Construction and Application of Ubiquitin-Derived Activity-Based Probes of Deubiquitinases - Pawlak, Tomasz Maciej (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2026)
Deubiquitinases (DUBs) are critical regulators of ubiquitin signalling, with direct implications in cancer, neurodegeneration, inflammatory conditions, and autoimmune diseases. This thesis presents the development of novel chemical tools to study DUB function, combining radical-mediated bioconjugation strategies, bioorthogonal chemistry, and lysine-targeted warheads to create novel ubiquitin constructs. Building on the well-established thiol-yne reaction, a radical-based method for protein coupling was developed, enabling the first examples of linking two proteins via this approach. Using this radical thiol-yne strategy, a di-ubiquitin construct containing an internal alkene was generated. Although minor amounts of tri-ubiquitin were also formed via a thiol-ene reaction, steric hindrance largely suppressed trimer formation. As a result, access to the alkene was effectively restricted to small molecules, sterically compatible active-site cysteines in DUBs, and potentially other cysteine-containing ubiq-uitin-binding proteins. The di-ubiquitin probe was partially purified and successfully shown to label the cysteine protease DUB OTUB1 via a thiol-ene reaction, demonstrating promising, if modest, labelling that warrants further study. These findings reveal the potential of probes containing internal alkenes to label other cysteine proteases. Complementary approaches, utilising azido-modification of lysine side chains followed by azidealkyne cycloaddition, enabled the formation of ubiquitin dimers bearing terminal alkenes. Terminal alkenes were shown to undergo a thiol-ene reaction, providing proof of concept for combining these specific biorthogonal methods to achieve controlled protein crosslinking. To expand the repertoire of DUB-targeting probes, squaramide-functionalized ubiquitin constructs were developed, capable of covalently capturing DUBs via lysine residues near their active sites. These probes demonstrated activity against the metalloprotease DUB Rpn11, warranting further investigation to elucidate their binding interactions. Combining the bioorthogonal conjugation methods presented in this thesis shows promise for designing multifunctional, controllable ubiquitin-based probes to dissect DUB specificity and function. By integrating radical chemistry, bioorthogonal reactions, and lysine-reactive warheads, this work contributes a versatile chemical biology toolkit for probing ubiquitin signalling and advancing our understanding of the roles of DUB in biology.
APPROVED
Keywords: proteomics; chemical biology; Activity-Based Probes; lysine modification; cysteine modification; ubiquitin; radical chemistry; biocompatible; bioorthogonal; chemical modification; proteins